Design and experiment study on entricfugal-electrostatic air filter for single-cylinder diesel engine - CHEN Kai-kao; ZHENG Wen-zhong; HE Yong (浙江大学学报. 农业与生命科学版, 2003)
Aiming at shortcomings of air filter used currently in diesel engine, a new dust cleaning method, i. e. centrifugal-electrostatic filtration mechanism, was put forward on the base of analysis of the relation between dust cleaning method and dust radius. A centrifugal-electrostatic air filter was designed for type S195 diesel engine considering form, structure dimension and static electricity producing device. Results of test show that the filtration efficiency of air filter reaches to standard, power of diesel engine increases, and specific fuel consumption decreases by using the new air filter.